2017
DOI: 10.1038/ncomms14540
|View full text |Cite
|
Sign up to set email alerts
|

Electrically tunable artificial gauge potential for polaritons

Abstract: Neutral particles subject to artificial gauge potentials can behave as charged particles in magnetic fields. This fascinating premise has led to demonstrations of one-way waveguides, topologically protected edge states and Landau levels for photons. In ultracold neutral atoms, effective gauge fields have allowed the emulation of matter under strong magnetic fields leading to realization of Harper-Hofstadter and Haldane models. Here we show that application of perpendicular electric and magnetic fields effects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 33 publications
2
53
0
1
Order By: Relevance
“…We show that in conventional GaAs quantum wells containing charged impurities, an exciton flow may be reoriented in the real space due to the combined effect of the local electrostatic potential created by charged impurities and the magnetic field applied in normal to the plane direction. Conceptually, this effect is similar to the cross-field effect proposed by Imamolu [5,6] and it manifests itself in a very simi-lar phenomenology to the exciton Hall effect studied by Onga et al [7], however, it is different from both above mentionned effects as (i) an external electric field is not needed, (ii) spin-valley locking is not needed. To distinguish from the previous studies we refer to the effect we study as an anomalous exciton Hall effect.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…We show that in conventional GaAs quantum wells containing charged impurities, an exciton flow may be reoriented in the real space due to the combined effect of the local electrostatic potential created by charged impurities and the magnetic field applied in normal to the plane direction. Conceptually, this effect is similar to the cross-field effect proposed by Imamolu [5,6] and it manifests itself in a very simi-lar phenomenology to the exciton Hall effect studied by Onga et al [7], however, it is different from both above mentionned effects as (i) an external electric field is not needed, (ii) spin-valley locking is not needed. To distinguish from the previous studies we refer to the effect we study as an anomalous exciton Hall effect.…”
supporting
confidence: 74%
“…This effect is a manifestation of the Lorentz force that pulls an electron and a hole apart if an exciton as a whole particle moves in the presence of a magnetic field. Imamolu [5,6] pointed out that once an exciton is placed in crossed electric and magnetic fields, it starts moving as a whole in the direction perpendicular to the directions of both fields, that leads to the renormalization of the excitonic dispersion semiconductor quantum wells or two-dimensional semiconductor crystals. Onga et al [7] have recently reported the experimental observation of an exciton Hall effect in atomically thin layers of MoS 2 that manifests itself in the appearance of an off-diagonal exciton conductivity in the presence of a magnetic field.…”
mentioning
confidence: 99%
“…These gauge fields can be classified into Abelian (commutative) and non-Abelian (non-commutative) depending on the commutativity of the underlying group. Much success has been achieved in synthesizing Abelian gauge fields on different platforms, including cold atoms [2][3][4][5][6][7][8][9][10] , photons [11][12][13][14][15][16][17][18][19][20][21][22] , phonons [23][24][25] , polaritons 26 , and superconducting qubits [27][28][29] . It is more demanding to synthesize non-Abelian gauge fields because they require internal degrees of freedom and non-commutative matrix-valued gauge potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Such optical measurements allow for probing square micrometer scale areas with good spatial resolution that are inaccessible with global electrical measurements. Moreover, the polaritons are sensitive to magnetic fields due to the diamagnetic and Zeeman shifts [37,38], and based on our results we estimate magnetic field sensitivities on the order of 100 nT Hz −0.5 with 1 μW of incident power are achievable.…”
mentioning
confidence: 56%